Woodshedding in the middle school classroom - Enns, Darren (Kansas State University, 2018)
Students in a combined choir of 7th and 8th graders learned the basics of woodshedding, which is a technique that barbershop choirs use to add harmony to a melody without the use of written music. Building off of previous skills, particularly ear training through use of solfege and Curwen hand signs, students learned how to create their own vocal harmony with any given chord progression. Students demonstrated these skills by singing along with the melody, “You Are My Sunshine.” Through my courses at Kansas State University, two main areas of development have been, 1) continued growth in teaching beginners using Gordon’s Music Learning Theory (Gordon, 2012) and Curwen handsigns for ear training, 2) developing a culture of excellence that expands to all vocal students, teaching them strong character, work ethic, and musicianship for a lifetime of making music.
Keywords: Woodshedding; Middle school; Music; Singing; Choir